Pegylated Citric Acid Dendritic Architecture for the Delivery of Cytarabine in Targeting the Cancer Cells - B. Narasimha Rao, K. Ravindra Reddy, K. B. Chandra Sekhar (Journal of Applied Pharmaceutical Science, 2017)
Current progress in nanotechnology provides a new hope for the substantial development in the success of cancer therapy particularly in controlling tumor growth and development. PEGylated citric acid dendrimers are biocompatible compounds being developed with an aim to target the myeloid cells, from which leukemia starts and spreads. Developed dendrimers also overcome the limitations observed with usual cancer therapies like drug leakage during circulation and short circulation time in blood. Cytarabine, an antimetabolite antineoplastic agent was tightly encapsulated within the dendrimer through simple complexation and targeted to tumor cells by way of high affinity interactions. PEGylation prevents the drug leakage during circulation, bypasses RES uptake by opsonins and improves drug’s stability, circulation time when administered. In present study, PEGylated citric acid dendrimers were synthesized using Divergent technique and loaded with Cytarabine. Synthesized dendrimers were evaluated for different parameters like SEM, DSC, NMR, % drug entrapment and in-vitro drug release studies etc.
Keywords: Cytarabine, Acute myeloid leukemia, PEGylation, Antimetabolite, Generation.